Kymriah® (tisagenlecleucel) - An overview of the clinical development journey of the first approved CAR-T therapy - Rakesh Awasthi; Harald J. Maier; Jie Zhang; Stephen Lim (Taylor & Francis Group, 2023)
The emergence of cell and gene therapies has dramatically changed the treatment paradigm in oncology and other therapeutic areas. Kymriah® (tisagenlecleucel), a CD19-directed genetically modified autologous T-cell immunotherapy, is currently approved in major markets for the treatment of relapsed/refractory (r/r) pediatric and young adult acute lymphoblastic leukemia, r/r diffuse large B-cell lymphoma, and r/r follicular lymphoma. This article presents a high-level overview of the clinical development journey of tisagenlecleucel, including its efficacy outcomes and safety considerations.